Dorcadion axillare Küster, 1847 (Coleoptera, Cerambycidae): distribution, morphometrics, karyotype and description of a new subspecies from Romania - Dascălu, Maria-Magdalena; Fusu, Lucian (Zootaxa, 2012)
Dorcadion axillare Küster, 1847 is confirmed to be present in Romania more than one hundred years after the last pub-lished record. This species was mentioned in 1908 from several localities in SE Romania by A. L. Montandon, but thisrecord was overlooked or misinterpreted by subsequent authors, the species being currently considered endemic for Bul-garia. Based on all published records, museum specimens and new collecting data, D. axillare is in fact widely distributedin Romania. The specimens from the northern part of the distribution area differ from those in Bulgaria and are consideredto belong to a different subspecies, D. axillare moldavicum ssp. nov. The cytogenetic study has revealed a karyotype with 2n = 24 and this is the first comprehensive information on the chromosomes of the genus Dorcadion.